Cardiac Fibroelastoma: A Rare Cause of Stroke in Young Adults - Ahmad Mirdamadi; Mohsen MirmohammadSadeghi; Mahfar Arasteh; Mojgan Gharipour (Case Reports in Cardiology)
A 26-year-old man presenting with a transient episode of dysarthria and dizziness, 3 weeks prior to admission, was referred to our center to be evaluated for transient ischemic attack (TIA). The patient had been previously admitted to a different hospital and echocardiography was reported normal at that center, but upon presenting to our institution strand-like masses in the left ventricle (LV) were detected. Transesophageal echocardiography (TEE) revealed two distinct mobile LV masses suggesting a diagnosis of papillary fibroelastoma. CT angiography and histopathological studies confirmed this diagnosis.